Antibody-drug conjugates in metastatic triple negative breast cancer: a spotlight on sacituzumab govitecan, ladiratuzumab vedotin, and trastuzumab deruxtecan. (3rd July 2021) - McGuinness, Julia E.; Kalinsky, Kevin
ABSTRACT: Introduction: Metastatic triple-negative breast cancers (mTNBC) are characterized by aggressive behavior and worse clinical outcomes than other breast cancer subtypes, as well as poor response to cytotoxic chemotherapies. The use of antibody-drug conjugates (ADCs) has been investigated as a potential treatment strategy, particularly in heavily pretreated disease. Areas covered: This article reviews the preclinical and clinical data supporting the use of the ADCs sacituzumab govitecan (SG), ladiratuzumab vedotin (LV), and trastuzumab deruxtecan (T-DXd) in mTNBC, and highlights ongoing clinical trials and future clinical applications. Expert opinion: SG, LV, and T-DXd have demonstrated their potential to meaningfully improve clinical outcomes in patients with pretreated mTNBC, as demonstrated by notable response rates in phase I/II and, for SG, phase III clinical trials. Investigation of their use in combination with other agents, including PARP inhibitors and checkpoint inhibitors, is ongoing in the metastatic setting, and their application in early-stage TNBCs are under investigation. ADCs are therefore expected to redefine treatment paradigms in TNBC.